Verbena (Glandularia sp.) breeding in Argentina - Bologna, Paula; Soto, Maria Silvina; Escandon, Alejandro Salvio; Ianicelli, Jesica; Perez De La Torre, Mariana; Alderete, Marisol; Tombion, Leticia (Springer, 2025)
Glandularia genus is an herbaceous pennenial plant that belongs to the Verbenaceae family. In Argentina we can find 36 species and one botanical variety. Although it is an american genus, specimen of these plants has long been cultivated throughout the world under the Verbena denomination even though they are two separate genera. Studies in the genus have been done to demonstrate the compatibility between the species, but the genetic background of the cultivated hybrids are difficult to determine because of the taxonomic controversy plus the occurrence of natural hybrids in nature. The Instituto de Floricultura in Argentina (INTA) has developed the first Glandularia cultivars from native germplasm. Following the methodology of germplasm collection, domestication, characterization, crossing and selection of elite material and ending with the registration of cultivars at the Instituto Nacional de Semillas, nowadays the national market has a supply of cultivars with hardy and vigorous performance. Within the breeding process, biotechnology tools have been used on the genus at the Instituto de Floricultura of INTA. Studies in micropropagation, mutation breeding to obtain polyploids, and molecular markers have been done in the research of the genus. This was useful to develop a traceability system with the aim to protect the genetics of the cultivars and to maintain plants free of viruses. Besides the cultivars developed, the breeding in this genus tends towards a compact plant form, a continuous flowering and heat tolerance. Beside Glandularia genus used for ornamental purposes, it has a great potential to be used as a functional plant in agroecological crops because of its rusticity and affinity for attracting beneficial insects.